Collaborative Governance in the Restorative Justice House Program - Suacana, I Wayan Gede; Sudana, I Wayan; Wiratmaja, I Nyoman; Gianyar, I Made; Rukmawati, Diah (Jurnal Pengabdian Masyarakat Bestari, 2024)
The restorative justice house program in Sumerta Kelod Village, East Denpasar District, Denpasar City, represents innovation in conflict resolution at the local level. This article aims to explore the implementation of tata kelola pemerintahan kolaborasi in the context of the program and evaluate its impact on the sustainability and effectiveness of the program. Community Partnership Program Implementation Activities are divided into three stages, namely preparation, implementation, and monitoring and evaluation stages. The results of the PKM implementation show that the Tata kelola pemerintahan kolaborasi Model in the Rumah Restorative Justice Program is quite effective in improving the inclusive and participatory decision-making process in Sumerta Kelod Village. This emphasizes the importance of integrating various interests and resources to achieve common goals in strengthening collaboration, capacity development and monitoring and evaluation effectiveness. Collaboration between the village government and various other parties in implementing the Restorative Justice Program is an important step to create a more just, peaceful and harmonious environment at the village level. Restorative Justice, which emphasizes restoration of losses and reconciliation between perpetrators, victims and society, requires a participatory and inclusive approach. This collaboration not only increases the effectiveness of the program but also ensures that the results reflect the interests and needs of the entire village community.